2012
DOI: 10.3390/ijms13055917
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Biosynthetic Potential of Culturable Actinomycetes Associated with Marine Sponges in the China Seas

Abstract: The diversity and secondary metabolite potential of culturable actinomycetes associated with eight different marine sponges collected from the South China Sea and the Yellow sea were investigated. A total of 327 strains were isolated and 108 representative isolates were selected for phylogenetic analysis. Ten families and 13 genera of Actinomycetales were detected, among which five genera represent first records isolated from marine sponges. Oligotrophic medium M5 (water agar) proved to be efficient for select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 64 publications
0
36
0
1
Order By: Relevance
“…This could be helpful for the discovery of new antibiotic producers and the exploitation and utilization of new, biologically active compounds. Previous researches had proved that oligotrophic media could positively influence the isolation of actinomycetes [10,11]. While no research have made systematic comparison between standard medium and the corresponding oligotrophic medium to study the specific effect of oligotrophy on actinomycetes isolation, which was studied in this research.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This could be helpful for the discovery of new antibiotic producers and the exploitation and utilization of new, biologically active compounds. Previous researches had proved that oligotrophic media could positively influence the isolation of actinomycetes [10,11]. While no research have made systematic comparison between standard medium and the corresponding oligotrophic medium to study the specific effect of oligotrophy on actinomycetes isolation, which was studied in this research.…”
Section: Discussionmentioning
confidence: 98%
“…However, oligotrophic media prevent the overgrowth of eutrophic and fast-growing actinomycetes, which provide oligotrophic actinomycetes with suitable nutrients concentration and sufficient growing space. Previous researches indicated that oligotrophy is an important way to explore unknown actinomycete resources [10,11]. We should pay more attention to the comprehensive study of the improving effects of oligotrophy on the actinomycetes isolation.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still few studies involving the search for these genes in actinobacteria. Xi et al (2012) estimated that 27.5% of the isolates tested that belonged to the genus Streptomyces (34 isolates) showed antimicrobial activity, and it has been shown that the strains where both pks and nrps genes were identified produced a significantly higher number of secondary metabolites. Zhong et al (2013) demonstrated the assembly and features of secondary metabolite biosynthetic gene clusters with pks and nrps in S. ansochromogenes.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive laboratory analyses done on sponge associated actinomycetes has found that a number of different species are culturable from marine sponges, and that they are capable of producing bioactive secondary metabolites (Schneemann et al, 2010; Xi et al, 2012). With respect to the sponge Halichondria panicea , for example, five actinomycete genera were isolated and the bacterial extracts were found to contain secondary metabolites with bioactivities (Schneemann et al, 2010).…”
Section: Actinomycete Natural Products In Marine Organismsmentioning
confidence: 99%